HPLC Method for Quantification of Ornidazole in Human Plasma - Sam Solomon, W.D.; Veeran Gowda, K.; Senthamil Selvan, P.; Mandal, U.; Pal, T.K. (Asian Journal of Chemistry, 2010)
A sensitive and rapid reverse phase HPLC method was developed to quantify plasma levels of ornidazole, to evaluate a comparative bioavailability study. The drug and internal standard were purified from plasma samples by liquid-liquid extraction using dichloromethane. The HPLC separation was performed on BDS hypersil C18 column (250 × 4.6 mm, 5 μ), using 0.05 M disodium hydrogen phosphate (pH 4.8) and acetonitrile (60:40 v/v) with a flow rate of 1 mL/min and UV detection at 313 nm. Standard curve covering 50 ng-12 μg/mL concentration range, was linear (r2 = 0.9997). The precision and accuracy of ornidazole was 3.52 > % RSD and 3.6 > % RME in intra-day and inter-day analysis after four quality control very low, low, medium and high (QCVL, QCL, QCM and QCH) samples. The bio-study was carried out in 12 healthy human volunteers according to a single dose, twosequence, cross over randomized design. The 90 % confidence interval for the ratio of the logarithmic transformed AUC0-∞ (0.83-1.02) and Cmax (0.93-1.03) were within the bioequivalence limit of 0.80-1.25.